2013
DOI: 10.1089/ten.tea.2012.0644
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multifunctional Polysaccharide Hydrogels with Varying Stiffness for Bone Tissue Engineering

Abstract: The use of hydrogels for bone regeneration has been limited due to their inherent low modulus to support cell adhesion and proliferation as well as their susceptibility to bacterial infections at the wound site. To overcome these limitations, we evaluated multifunctional polysaccharide hydrogels of varying stiffness to obtain the optimum stiffness at which the gels (1) induce proliferation of human dermal fibroblasts, human umbilical vascular endothelial cells (HUVECs), and murine preosteoblasts (MC3T3-E1), (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 90 publications
1
30
0
Order By: Relevance
“…The Campos group has used a fibrin-agarose material for engineering a variety of tissues including peripheral nerves, skin, oral mucosa, and corneas [40][41][42][43][44][45]. Others are investigating collagen-agarose gels for skin tissue engineering [46] or in combination with methylcellulose and chitosan for bone tissue engineering [47].…”
Section: Agarose As a Tissue Engineering Scaffoldmentioning
confidence: 99%
“…The Campos group has used a fibrin-agarose material for engineering a variety of tissues including peripheral nerves, skin, oral mucosa, and corneas [40][41][42][43][44][45]. Others are investigating collagen-agarose gels for skin tissue engineering [46] or in combination with methylcellulose and chitosan for bone tissue engineering [47].…”
Section: Agarose As a Tissue Engineering Scaffoldmentioning
confidence: 99%
“…The mechanical properties of engineered substrates also play a key role, as the osteogenic phenotype of mesenchymal progenitors is induced by stiff substrates with an elasticity ranging from 25 to 40 kPa, corresponding to stiffness in physiological osteoid [34]. More recent studies highlight the complexity of the underlying mechanisms, since material stiffness can differentially regulate (i) osteogenic cell phenotypes, depending on the specific stage of differentiation [35,36] and (ii) polarization of macrophages, in turn regulating the process of bone healing [37].…”
Section: Rationale For the Use Of Ecm In Bone Regenerationmentioning
confidence: 99%
“…Inorganic nanoparticles incorporated to a polymeric network have thus been shown to improve an array of properties of the pure polymer, including stiffness, resistance to wear and crack propagation, compressive load-bearing capacity, overall stability and even tensile strength 83 . Studies have shown that osteoblasts proliferate better on surfaces stiffer than most polymers 84 as well as that mesenchymal stem cells (MSCs) differentiate into neurons on soft surfaces and osteoblasts on the stiff ones 85 , which explains how come the dispersion of CAP particles throughout a polymeric matrix leads to an increased Young’s modulus and increased bioactivity of the composite material at the same time 86 . Moreover, it is a rule of thumb that biomaterials in general should be rough so as to promote cell attachment 87,88 , except in a few cases, including joint and some soft tissue implants for which smooth surfaces are more desirable; impregnation of polymers with inorganic nanoparticles contributes to this surface roughness and makes additional processing steps such as etching or sandblasting unnecessary.…”
Section: Polymeric/cap Compositesmentioning
confidence: 99%